2020
DOI: 10.24191/jcrinn.v5i2.163
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Intention to use E-learning from Students’ Point of View- An Evidence from Malaysia Local University

Abstract: Education landscape has changed dramatically due to Covid19 pandemic as in many country, conventional or face-to-face teaching and learning is no longer an option to avoid the spread of a virus.  E-learning become one of the best alternative to ensure education process could continue because experts believe world could only recover from this crisis in another two years. This paper will delve into students’ perspective about e-learning and their willingness to use e-learning. Technology Acceptance Model (TAM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In fact, most of these studies focused on the two more influential constructs, which are the perceived ease of use and the perceived usefulness. The studies have adhered to the effective role of these two constructs in making students' adoption or acceptance is on-demand [40,[42][43][44]. The extended model of TAM that UTAUT has also been used as a model to measure the effectiveness of the constructs during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, most of these studies focused on the two more influential constructs, which are the perceived ease of use and the perceived usefulness. The studies have adhered to the effective role of these two constructs in making students' adoption or acceptance is on-demand [40,[42][43][44]. The extended model of TAM that UTAUT has also been used as a model to measure the effectiveness of the constructs during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a way that guarantees that the change from the traditional class to the e-learning environment is safe and effective [2,3]. By the end, all these in these educational institutions can achieve their goals and objectives [44,45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, the students also find that e-learning does not affect their learning costs since both methods cause them to spend the same amount of money. However, they do have concerns about the employers' acceptance, which is similar to Mad et al (2020), who found 59 percent of the respondents afraid that they will face discrimination during the employment selection process caused by offline teaching and learning. On the other hand, students' perceived usefulness and attitude toward e-learning had a significant impact on the intention to use elearning for mathematics courses.…”
Section: Discussionmentioning
confidence: 64%
“…An e-learning system is not something new, but at the same time, it is also a complex system. Mad et al (2020) find that most students do not like the idea of e-learning because of the doubt in technology advancement in Malaysia. It is a big challenge to change the way one has been learning for years to a newly introduced system.…”
Section: Discussionmentioning
confidence: 98%
“…The current COVID-19 pandemic has negatively affected the education of almost 90% of the world’s student population (Monasterio & Briceño, 2020 ), mainly because most institutions decided to avoid in-person classes, in order to prevent the spread of the virus in the different educational contexts. This pandemic has forced a rushed adaptation and migration of the teaching process to an online context, which added to the few digital skills both teachers and students possess (Fardoun et al, 2020 ), the weak technological infrastructure in institutions, and the lack of processes to support virtual education (Mad et al, 2020 ), has made teaching more complex, and it has made to use of ICTs and improvisation the main characteristics of the current teaching-learning process (Ríos, 2020 ).…”
Section: Introductionmentioning
confidence: 99%